2018
DOI: 10.31557/apjcb.2018.3.2.37-45
|View full text |Cite
|
Sign up to set email alerts
|

HLA-G: Facts and Fictions

Abstract: Human leukocyte antigen (HLA)-G is a nonclassical MHC class I molecule with modulatory effects on NK and T cells. Unlike classical HLA class I molecules, HLA-G has seven isoforms, three of which are soluble. Soluble HLA-G molecules are reportedly able to transduce negative signals to immune cells after interacting with their corresponding receptors. The expression of these molecules plays significant roles in maternal tolerance against semi-allogenic fetuses. Overexpression of HLA-G in tumors and increased ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 90 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…These articles were published between 1998 and 2020, among which 20 were conducted in China, 3 were conducted in Japan, 1 was conducted in Turkey, 2 were conducted in the Netherlands, 2 were conducted in Iran, 1 was conducted in Australia, and 1 was conducted in Italy. Of the 30 articles included in the meta-analysis, there were 12 studies on CRC (24, 30-36, 38, 43, 45, 46), 6 studies on GC (25,28,39,41,42,47), 5 studies on ESCC (7,12,(48)(49)(50), 5 studies on HCC (26,27,29,37,51), and 2 studies on PC (52,53). Among them, one study specifically addressed COAD (31), one study addressed RC (30), and one addressed both HCC and PAAD (37).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These articles were published between 1998 and 2020, among which 20 were conducted in China, 3 were conducted in Japan, 1 was conducted in Turkey, 2 were conducted in the Netherlands, 2 were conducted in Iran, 1 was conducted in Australia, and 1 was conducted in Italy. Of the 30 articles included in the meta-analysis, there were 12 studies on CRC (24, 30-36, 38, 43, 45, 46), 6 studies on GC (25,28,39,41,42,47), 5 studies on ESCC (7,12,(48)(49)(50), 5 studies on HCC (26,27,29,37,51), and 2 studies on PC (52,53). Among them, one study specifically addressed COAD (31), one study addressed RC (30), and one addressed both HCC and PAAD (37).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The potential relationship between tumor cells and their microenvironment, including immune system components, plays an important role in the development, growth and spread of GI cancers (21)(22)(23). Studies on the prognostic value of HLA-G and its association with clinicopathological parameters in GI cancer patients have presented conflicting results (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). Some studies have demonstrated that positive HLA-G expression or increased levels of circulating sHLA-G are associated with unfavorable survival (24, 25, 27-29, 32, 34, 35, 37, 39), while others have found no significant association (31,36,38,40,41).…”
Section: Introductionmentioning
confidence: 99%